Fluoxetine Prevents Aβ1-42-Induced Toxicity via a Paracrine Signaling Mediated by Transforming-Growth-Factor-β1 - Caraci, Filippo; Tascedda, Fabio; Merlo, Sara; Benatti, Cristina; Spampinato, Simona F.; Munafò, Antonio; Leggio, Gian Marco; Nicoletti, Ferdinando; Brunello, Nicoletta; Drago, Filippo; Sortino, Maria Angela; Copani, Agata (Frontiers in Pharmacology, 2016)
Selective reuptake inhibitors (SSRIs), such as fluoxetine and sertraline, increase circulating Transforming-Growth-Factor-β1 (TGF-ß1) levels in depressed patients,and are currently studied for their neuroprotective properties in Alzheimer’s disease (AD). TGF-β1 is an anti-inflammatory cytokine that exerts neuroprotective effects against ß-amyloid (Aβ)-induced neurodegeneration. In the present work the SSRI, fluoxetine, was tested for the ability to protect cortical neurons against 1µM oligomeric Aß1-42-induced toxicity. At therapeutic concentrations (100nM-1µM), fluoxetine significantly prevented Aβ-induced toxicity in mixed glia-neuronalcultures, but not in pure neuronal cultures. Though to a lesser extent, also sertraline was neuroprotective in mixed cultures, whereas serotonin (10nM-10µM) did not mimick fluoxetine effects. Glia-conditioned medium collected from astrocytes challenged with fluoxetine protected pure cortical neurons against Aβ toxicity. The effect was lost in the presence of a neutralizing antibody against TGF-ß1 in the conditioned medium, or when the specific inhibitor of type-1 TGF-β1 receptor, SB431542, was added to pure neuronal cultures. Accordingly, a 24 hr treatment of cortical astrocytes with fluoxetine promoted the release of active TGF-β1 in the culture media through the conversion of latent TGF-ß1 to mature TGF-ß1. Unlike fluoxetine, both serotonin and sertraline did not stimulate the astrocyte release of active TGF-β1. We conclude that fluoxetine is neuroprotective against Aß toxicity via a paracrine signaling mediated by TGFβ-1, which does not result from a simplistic SERT blockade.